Tony Harrison’s Adaptation of Phaedra’s Moral Conflict: Phaedra Britannica - Florentina Gümüş (Litera: Dil, Edebiyat ve Kültür Araştırmaları Dergisi)
This essay sets out to discuss Tony Harrison’s play Phaedra Britannica (1975) by drawing primarily on Linda Hutcheon’s views as expressed in her theory of adaptation and Harrison’s own insights into adaptation. In this discussion, Phaedra Britannica as an adaptation of Jean Racine’s Phèdre (1677), is understood as the outcome of an evolutionary process which started with ancient cultures and, at the same time, as an autonomous work. In order to make the story of Phaedra relevant for contemporary audiences, Harrison sets his play in a colonial context, during the British occupation of India. This essay addresses the adaptation of the play through the moral conflict associated with the story of Phaedra, a woman in love with her stepson Hippolytus, with a focus on shame and guilt. Throughout the centuries, these moral concepts have played a significant role in the story. The culture in Racine’s Phèdre has been described as one dominated by guilt, but in Harrison’s play a return to the shame culture depicted in Hippolytus by Euripides can be observed. Unlike Euripides, who is ambiguous about the role of gods, goddesses and fate, Harrison makes it clear that the characters’ attempts at assigning blame to other people or to the gods of the colonised territory is simply their way of deflecting responsibility for the tragic events.